PENGARUH KARAKTERISTIK TUJUAN ANGGARAN TERHADAP KINERJA PEMERINTAH DAERAH DI KABUPATEN PELALAWAN - Intan Dwirianti; Kirmizi Ritonga; Al Azhar Ali (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This study aims to examine: 1) the effect of budget participation on local government performance, 2) the influence of clarity of purpose budget of local government performance, 3) the effect of feedback on the performance of local government budget, 4) the effect on the performance evaluation of local government budgets and 5) influence difficulty budgetary purposes of local government performance. The sample used in this study is that there are agencies in Pelalawan. Collecting data through a questionnaire survey method. Of the 68 questionnaires distributed, the number of questionnaires returned was 52. The data using multiple regression analysis (multiple regression) with the help of a computer program SPSS version 17.0. The results showed that: 1) Budget Participation no significant effect on the performance of Local Government, 2) Clarity of Purpose Budget significant effect on the performance of Local Government, 3) Feedback Articles significant effect on the Local Government Performance, 4) Evaluation Budget significant effect on government performance areas and 5) Difficulty Purpose Budget significant effect on the performance of Local Government. It can be concluded that the coefficient of determination 0666 or 6.66%. Figures 6.66% explained that performance is affected by the participation of local government budget, clarity of purpose budget, budget evaluation, feedback and difficult budget budgetary purposes. 33.4% while the remaining local government performance is explained by other variables not included in this study.Keywords: Budgetary, Performance, and Government.